Britain and Europe on the geopolitical roller-coaster. (June 2017) - Callinicos, Alex
This article analyses the geopolitical significance of Brexit. It argues that, together with Donald Trump's election as President of the United States, it represents the historical moment when the twin crises that emerged in 2008 – the re-emergence of Russia as a geopolitical challenger to the United States and the financial crash that exposed the fragility of the neoliberal economic system – effectively fused. The article explores the double imperial constitution of the European Union, Britain's peculiar positioning within global power structures, and the combined impact of the crash, the Great Recession of 2008–2009, and the policy reaction of seeking to recharge neoliberalism through austerity as creating the conditions for the Brexit vote. Now elites in Britain, the rest of the European Union, and the US must grapple with the direct circuit that has been established between domestic socio-political tensions and geopolitical antagonisms.